KAJIAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI PERSAMAAN GARIS LURUS DI KELAS VIII SMP NEGERI 6 PALANGKA RAYA - Dina Damiyanti Hidayat; Walter Punding; Sugiharto . (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
This research is motivated by the low problem solving ability of students in solving straight line equations. The purpose of this study was to describe the mathematical problem solving ability of students on the material of straight line equations in class VIII-9 SMP Negeri 6 Palangka Raya. The subjects of this study were students of class VIII-9 of SMP Negeri 6 Palangka Raya out of 33 students only 26 students took the test. Then from 26 students 3 students were taken with high, medium, and high abilities, low to be interviewed. Based on the results of data analysis of students mathematicaproblemsolving abilities in solving straight line equations from 26 students, it was obtained that 2 students had problem solving abilities that were included in the